2011
DOI: 10.4103/0974-777x.81687
|View full text |Cite
|
Sign up to set email alerts
|

Awareness regarding the systemic effects of periodontal disease among medical interns in India

Abstract: Background:Medical curriculum does not provide required space for oral health; hence, many medical interns are unfamiliar with the oral cavity and oral health research.Aims:To study the level of awareness regarding systemic effects of periodontal disease among medical interns.Settings and design:A cross-sectional qualitative study recruiting medical interns from two medical institutions affiliated to two different universities in Southern India.Materials and Methods:Study was carried out in two medical institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…Despite this low awareness level, the majority of the participants knew that performing non-surgical periodontal treatment has an effect on reducing systemic inflammatory mediators which increased the probability and risk of developing CVDs. Our results are similar to the study by Gur and Majra (2011) [42] who reported that only 12%-16% of medical interns thought that PD may be a possible risk factor to develop CVD or cerebral infarction. However, our results are in contrast to other studies (Asa'ad et al, 2014, Quijano et al, 2010 who found that the majority of medical interns agreed that poor oral health may increase the risk of CVD.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Despite this low awareness level, the majority of the participants knew that performing non-surgical periodontal treatment has an effect on reducing systemic inflammatory mediators which increased the probability and risk of developing CVDs. Our results are similar to the study by Gur and Majra (2011) [42] who reported that only 12%-16% of medical interns thought that PD may be a possible risk factor to develop CVD or cerebral infarction. However, our results are in contrast to other studies (Asa'ad et al, 2014, Quijano et al, 2010 who found that the majority of medical interns agreed that poor oral health may increase the risk of CVD.…”
Section: Discussionsupporting
confidence: 92%
“…There was a very low level of knowledge related to active PD possibly being a risk for preterm delivery and low birth weight. Our results are supported by Gur and Majra (2011) [42] but in contrast to Asa'ad, et al (2014) [36] who reported some awareness in medical interns. In contrast to our study, Cohen et al (2015) [40] in their study of obstetricians and/or gynecologists, found that majority had correct knowledge of the role of bacteria in periodontal diseases.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As a result, medical physicians did not have sufficient knowledge about the systemic effects of periodontal disease. Therefore, medical and dental training was recommended (13).…”
Section: Discussionmentioning
confidence: 99%
“…ders such as coronary heart disease, (angina, myocardial infarction, and atherosclerosis) stroke, diabetes, premature birth (newborns with low birth weight), hospital pneumonia, and osteoporosis have been clearly demonstrated. Precise treatment of periodontal diseases has also been found to have positive effects on the management of these systemic conditions (11,13,(15)(16)(17). Several studies have investigated the knowledge of different groups of health care professionals about the relationship between periodontal disease and systemic conditions.…”
Section: Discussionmentioning
confidence: 99%